Malaysian consumers' willingness to choose Islamic mortgage products An extension of the theory of interpersonal behaviour - Amin, H; Abdul-Rahman, AR; Abdul-Razak, D (Emerald Group Publishing Ltd, 2024)
Indexed by Scopus